Logging Training Centre Batote Jammu and Kashmir - Singh, S. Niranjan (Indian Forester, 1959)
This note gives the salient features of the main activities of the logging training centre Batote, which functioned from 15th March to 18th July 1958. Information regarding basic logging equipment, additional logging equipment and mechanized equipment are given for wider information of forest officers and forest lessees in India.